Uloga institucije ombudsmena i sudova u sudskim postupcima povodom slučajeva diskriminacije u Bosni i Hercegovini - Čaušević, Mirza (Array, 2019)
When reading the article’s title, it is important to emphasize the role and importance of the Institution of the Ombudsman for Human Rights of Bosnia and Herzegovina, the most important national institution for the protection of human rights and fundamental freedoms. Consequently, according to the logic of thinking, it can be clearly concluded that the most important segment of action, above mentioned national institution, is to prevent or eliminate all forms of indirect and direct discrimination. Accordingly, the author decided, in addition to introductory and concluding considerations, to divide the article into four (4) parts. The first part of the article entitled “Theoretical Determination of Discrimination” provides general information on the concept, different forms and types of discrimination in accordance with the Law on Prohibition of Discrimination in Bosnia and Herzegovina. Unlike the first, in the second part of the article “The Role of the Ombudsman in the Probation of Discrimination Proceedings”, the Ombudsman aims to present the legal position of the ombudsman in court proceedings, with the mandatory indication of the conditions for initiating the proceedings on his own behalf, representing the individual and intervening in the ongoing proceedings. Through practical examples, the author seeks to emphasize the importance, role and importance of the ombudsman in court proceedings. Subsequently, in the third part of the “Role of Courts in the Probation of Discrimination Proceedings”, the author concentrates that, by using the Law on Prohibition of Discrimination, he presents court judgments that discriminate the education system of the Central Bosnia and Herzegovina Canton (non) discriminatory on the basis of the existing segregation in so called. “Two schools under one roof”. Thus, this section primarily analyzes the rejection of the aforementioned claims.